1987
DOI: 10.1177/00220345870660021101
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny and Senescence of Salivary Immunity

Abstract: The objective of the present study was to evaluate the capacity for secretory immune responses throughout life. This was done by measuring, by single radial immunodiffusion, the concentrations of IgA and IgA1 subclass in saliva samples of subjects who ranged in age from two months to 91 years. The presence of salivary IgA antibodies to two nearly ubiquitous mucosal antigens, Streptococcus mutans glucosyltransferase (GTF) and killed poliovirus (Types 1, 2, and 3), was measured in an enzyme-linked immunosorbent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 25 publications
2
24
0
2
Order By: Relevance
“…The mucus membranes of hair cells, which play an important role in removing pathogens, are reduced in quantity and movement, as well as presenting ultra structural changes (Kim et al 2007). Immunoglobulin (Ig) A, the main constituent in secretions, levels increase up to 60 years old and thereafter a significant reduction in levels begins (Jafarzadeh et al 2010, Smith et al 1987, Ebersole and Steff en 1989. Therefore, structural and physiologic changes occur as a consequence of intrinsic aging combined with the environment can produce a marked susceptibility to dermatologic disorders in the elderly.…”
Section: Skin and Mucousmentioning
confidence: 99%
“…The mucus membranes of hair cells, which play an important role in removing pathogens, are reduced in quantity and movement, as well as presenting ultra structural changes (Kim et al 2007). Immunoglobulin (Ig) A, the main constituent in secretions, levels increase up to 60 years old and thereafter a significant reduction in levels begins (Jafarzadeh et al 2010, Smith et al 1987, Ebersole and Steff en 1989. Therefore, structural and physiologic changes occur as a consequence of intrinsic aging combined with the environment can produce a marked susceptibility to dermatologic disorders in the elderly.…”
Section: Skin and Mucousmentioning
confidence: 99%
“…However, low levels of IgA in saliva are known as a factor in infectious diseases such as upper respiratory infection. 35 In addition, it has also been reported that IgA levels in saliva could be decreased by psychological stress. [14][15][16][17] Hence, the fabricated OFET device could be applied for the monitoring of IgA levels for these health conditions in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a lower concentration of sIgA in saliva has been conceptualized as a risk factor for upper respiratory infection in children and the elderly. 20,21 Also, the value remarkably decreases under mental stress. The calibration curve of the standard sIgA from the lab-on-a-Disk for EIA is shown in Fig.…”
Section: Measurement Of Siga Using a Lab-on-a-diskmentioning
confidence: 92%